(untitled) (Al-Academy, 2022)
Perhaps going to watch movies in cinemas today has become different from what it was before. The cinematic film, the clarity of the image and the luster of its colors pulled the rug out from under the most important change that occurred in the structure of the contemporary cinematography, which is the sound. The surround sound environment that immerses viewers in the realism of sound that reaches them from all directions, and for this the researcher found it necessary to shed light on this topic because of its importance, so the research problem was represented in the following question: (How are modern sound systems used in the structure of contemporary feature films?) The theoretical framework included two topics: the first: the dialectic of the relationship between sound and image, and the second: the use of modern digital audio technologies in the feature film. While the research procedures, the descriptive-analytical approach was taken, and an intentional sample that meets the research objectives, which included the movie (John wick) in its three parts. The study concluded a number of results and conclusions.